2020
DOI: 10.1186/s12885-020-07064-0
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index increases the lymph node metastasis risk of breast cancer: a dose-response meta-analysis with 52904 subjects from 20 cohort studies

Abstract: Background: Since body mass index (BMI) is a convincing risk factor for breast cancer, it is speculated to be associated with lymph node metastasis. However, epidemiological studies are inconclusive. Therefore, this study was conducted to investigate the effect of BMI on the lymph node metastasis risk of breast cancer. Methods: Cohort studies that evaluating BMI and lymph node metastasis in breast cancer were selected through various databases including PubMed, PubMed Central (PMC), Web of science, the China N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 71 publications
1
15
1
Order By: Relevance
“…The American Cancer Society’s Cancer Prevention Study II, which followed 495 477 women from 1982 to 1998, reported a positive association between BMI and BC mortality: women with a BMI of 40 kg/m 2 had more than a two-fold increased risk of death compared with those with a BMI of 18 to 24.9 kg/m 2 ( 57 ). Moreover, a meta-analysis of 52 904 subjects showed that BMI increased the LN metastasis risk of BC, and for every 1 kg/m 2 increment in BMI, the risk of LN metastasis increased by 0.89 ( 58 ). This may be attributed to the increase in pro-inflammatory cytokines in the local and circulation caused by the high BMI, which promotes tumor growth, angiogenesis, invasion, and metastasis ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…The American Cancer Society’s Cancer Prevention Study II, which followed 495 477 women from 1982 to 1998, reported a positive association between BMI and BC mortality: women with a BMI of 40 kg/m 2 had more than a two-fold increased risk of death compared with those with a BMI of 18 to 24.9 kg/m 2 ( 57 ). Moreover, a meta-analysis of 52 904 subjects showed that BMI increased the LN metastasis risk of BC, and for every 1 kg/m 2 increment in BMI, the risk of LN metastasis increased by 0.89 ( 58 ). This may be attributed to the increase in pro-inflammatory cytokines in the local and circulation caused by the high BMI, which promotes tumor growth, angiogenesis, invasion, and metastasis ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20]. Previous studies have shown that clinico-pathological features such as size, age at diagnosis, palpable mass or not, body mass index (BMI) and hormone receptors are related to ALNM [21][22]. However, in our study, we aimed to compare the incidence of SLNM and ALNM based on the quadrant of breast and size of tumor in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Chlebowski determined that there was a lower risk of breast cancer in post-menopausal women who lose weight. [10] Blackburn determined in the Women's Intervention Nutrition Study that risk of breast cancer recurrence was reduced 24% in women who lost an average of 6 lbs. with a low fat diet intervention over those who had regular care.…”
Section: Discussionmentioning
confidence: 99%